Intraocular Pressure and its Variation with Total Amount of Energy used Following Nd: YAG Capsulotomy in Pseudophakic - Maryam Jabbar, Muhammad Siddique, Naseer Fatima, Faisal Rashid, Ammara Nasir, Abid Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The objective of the study was how Nd: YAG laser capsulotomy affected IOP and how it changed with the amount of energy utilised. Methods: A prospective, multi ccentered study was conducted between September 2021 to February 2022 in Ophthalmology Department departments. Total of sixty pseudophakic eyes of both genders, age ranging between 40 to 60 years with significant posterior capsular opacity following uncomplicated cataract surgery were included through non-probability purposive sampling technique. Inflammation, ocular malignancies, posterior segment disease, and systemic disease participants were all ruled excluded. After detailed history and ocular examination, Nd: YAG laser posterior capsulotomy was done. Patients were divided into two groups on the basis of total amount of laser energy used was noted as high energy (>50mJ) and low energy (<50mJ) and then post-laser IOP after one hour and 24 hours measured. Data was analyzed by using SPSS through repeated measure ANOVA for comparison of quantitative variables. Results: Best corrected visual acuity after Nd: YAG capsulotomy improved significantly (P=0.001). Pre-laser IOP was 14.01± 2.95 mmHg. Mean high energy was 76mJ and low energy 40mJ. Elevated IOP was seen in 55 patients, significantly increase in IOP after 1 hour in both groups (P=0.000). After 24hours IOP change was significantly higher in high energy group (p=0.033) than in low energy. Post-laser IOP after 1 hour in high energy group was 21.89±4.59 mmHg and in low energy group 16.79±2.89 mmHg. IOP after 24hour in high energy group was 19.89± 3.05 mmHg and in low energy group 14.98±1.79 mmHg. Conclusions: After Nd: YAG laser capsulotomy, there is a considerable increase in IOP, which varies depending on the overall amount of energy used. Greater the amount of Nd-YAG energy has significantly higher chances of raising IOP. Hence, it was suggested that each patient after Nd: YAG capsulotomy must monitored for IOP variation.